Artificial Aging Time Effect on Fatigue stress for Friction Stir Welded AA6061T6 (University of Thi-Qar Journal for Engineering Sciences, 2015)
This work involves studying the effect of heat treatment on the fatigue stress of friction stir welded joint of 6061T6 aluminum alloy. The microstructure,micro hardness , tensile and fatigue test of the welds and base alloy were examined before and after heat treatment which includes solution heat treatment at 500ºC and artificial aging at 190ºC for 2, 4, and 8 hrs.The friction stir welding was carried out by using CNC milling machine at constant tool rotational speed of (1000 rpm) and welding speed of (20mm/min),the fatigue test is investigated for all specimens to obtain the S-N curve. The results show that the heat treatment decreased fatigue strength for all elements comparing with base metal, while ageing at 2 hrs gives the best fatigue strength due to participated phases.